Resilience and Operational Sustainability of Oil Companies in Port Harcourt - Johnson, Ukpong Uwem; Nissi, Kalio; Ignatius, Ossai Onwusa (Journal of Advanced Research in Petroleum Technology & Management; Vol 4 No 3&4 (2018): Journal of Advanced Research in Petroleum Technology & Management, 2021)
We, in this paper, investigated the relationship between resilience and operational sustainability in the oil companies in Port Harcourt. The study adopted the cross-sectional survey research method and a quantitative methodology in its analysis of the distribution and relationship between the variables within the specified context of the study. The study engaged data generated from 207 employees in the oil companies; both descriptive and inferential statistical methods were adopted in the assessment of the manifestations and relationship between the variables. Empirical findings reveal that there is a positive significant relationship between resilience and quality and timeliness which measures operational sustainability. We recommended that resilience as expressed is needed for employees to activate their steadfastness to work goals irrespective of the challenges associated; and that behavior channeling and modification schemes that nurture positive psychological behavior amongst work members should be encouraged.